• решите

    (a+2b)^2-(a-b)(b+a)

    при а=1 b=0,2

Ответы 2

  • Ответ: 1

    Объяснение:

    =a^2+4ab+4b^2-(a^2-b^2)=a^2+4ab+4b^2-a^2+b^2=4ab+5b^2=4*1*0,2+5*0,04=0,8+0,2=1

    • Автор:

      oliveouwo
    • 5 лет назад
    • 0
  • Ответ:1

    Объяснение:

    (a+2b)^2-(a-b)(b+a)

    (1+2*0,2)^2-(1-0,2)(0,2+1)=(1+0,4)^2-(0,8*1,2)=1,4^2-0,96=1,96-0,96=1

  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years